Measuring mRNA copy-number in individual Escherichia coli cells using single-molecule fluorescent in situ hybridization (smFISH) - Skinner, Samuel O. (2013)
We present a method for measuring the absolute number of mRNA molecules from a gene of interest in individual, chemically fixed Escherichia coli cells. A set of fluorescently-labeled oligonucleotide probes are hybridized to the target mRNA, so that each mRNA molecule is decorated by a known number of fluorescent dyes. Cells are then imaged using fluorescence microscopy. The number of target mRNA is estimated from the total intensity of fluorescent foci in the cell, rather than from counting discrete “spots” as in other currently available protocols. Image analysis is performed using an automated algorithm. The measured mRNA copy-number distribution obtained from many individual cells can be used to extract the parameters of stochastic gene activity, namely the frequency and size of transcription bursts from the gene of interest. The experimental procedure takes 2 days, with another 2-3 days typically required for image and data analysis.